2017
DOI: 10.1186/s12959-017-0138-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ramadan fasting on platelet reactivity in diabetic patients treated with clopidogrel

Abstract: BackgroundThe effects of Ramadan fasting (RF) on clopidogrel antiplatelet inhibition were not previously investigated. The present study evaluated the influence of RF on platelet reactivity in patients with high cardiovascular risk (CVR) in particular those with type 2 diabetes mellitus (DM).MethodsA total of 98 stable patients with ≥2 CVR factors were recruited. All patients observed RF and were taking clopidogrel at a maintenance dose of 75 mg. Clinical findings and serum lipids data were recorded before Ram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Also, the relatively few MACEs in our study could be explained by the inhibited sympathetic tone during RF [13] and the limitation on smoking during Ramadan [14]. Bouida et al found that RF was significantly associated with diminished platelet sensitivity to clopidogrel in diabetic patients during and shortly after Ramadan [15]. This potential adverse effect of RF was not clinically evident in our study, mostly because we excluded most diabetic patients (uncontrolled DM, IDDM, and those with significant renal impairment).…”
Section: Discussionmentioning
confidence: 52%
“…Also, the relatively few MACEs in our study could be explained by the inhibited sympathetic tone during RF [13] and the limitation on smoking during Ramadan [14]. Bouida et al found that RF was significantly associated with diminished platelet sensitivity to clopidogrel in diabetic patients during and shortly after Ramadan [15]. This potential adverse effect of RF was not clinically evident in our study, mostly because we excluded most diabetic patients (uncontrolled DM, IDDM, and those with significant renal impairment).…”
Section: Discussionmentioning
confidence: 52%
“…In patients with T2 diabetes, dehydration can present as low blood pressure, lethargy, syncope, haemoconcentration and hypercoagulability predisposing to thrombosis [84] and strokes [85]. Although fasting can reduce platelet sensitivity to clopidogrel in T2 diabetes, this may be related to an increase in glycaemia during Ramadan [86]. However, it has been reported that the incidence of acute cardiac illness in patients with T2 diabetes is not different during Ramadan than at other times [87].…”
Section: Dehydration Thrombosis and Macrovascular Riskmentioning
confidence: 99%
“…However, a few studies showed no changes or even an increase in these parameters ( 10 – 17 ). Moreover, none of the studies showing reductions in these parameters considered potential confounders that may have affected their findings or explained the observed changes ( 13 , 14 , 18 20 ) and none targeted the general population.…”
Section: Introductionmentioning
confidence: 99%